Relationship between childhood blood pressure and birth weight - Sri Rahayu; Rusdidjas Rusdidjas; Rafita Ramayati; Oke Rina Ramayani; Rosmayanti Siregar (Paediatrica Indonesiana, 2015)
cardiovascular mortality and morbidity. Some studies havereported a significant relationship between elevated blood pressurein children with low birth weight.Objective To assess blood pressure differences in primary schoolstudents who had low and normal birth weights.Methods This cross-sectional study was conducted in 170children aged 6 to 12 years in March 2011 at a Medan primaryschool, North Sumatera. Blood pressure was measured with astandard mercury sphygmomanometer. A parental questionnairewas used to collect information on birth weight. Data wereanalyzed by student’s T-test for numerical data and Spearman’scorrelation test for a relationship between blood pressure andbirth weight.Results The subjects consisted of 85 children with low birth weightand 85 children with normal birth weight. The mean systolic (SBP)and diastolic blood pressures (DBP) were significantly higherin children with low birth weight than those with normal birthweight [SBP: 106.7 vs. 99.8 mmHg, respectively, (P=0.0001); andDBP: 69.2 vs. 63.5 mmHg, respectively, (P=0.0001)]. There wererelationships between elevated SBP and DBP and low birth weight,as indicated by correlation coefficient [r=-0.365 and r=-0.425,respectively, (P=0.0001)].Conclusion Blood pressure is significantly higher in children withlow birth weight than in those with normal birth weight. Birthweight was inversely related both to systolic and diastolic bloodpressure.